Are We There Yet? Exploring Empowerment at the Microscale in the South African Wine Industry. (August 2014) - Herman, Agatha
Empowerment is a standard but ambiguous element of development rhetoric and so, through the socially complex and contested terrain of South Africa, this paper explores its potential to contribute to inclusive development. Investigating microlevel engagements with the national strategy of Broad-Based Black Economic Empowerment (B-BBEE) in the South African wine industry highlights the limitations, but also potential, of this single-domain approach. However, latent paternalism, entrenched interests, and a 'dislocated blackness' maintain a complex racial politics that shapes both power relations and the opportunities for transformation within the industry. Nonetheless, while B-BBEE may not, in reality, be broad-based its manifestations are contributing to challenging racist structures and normalising changing attitudes. This paper concludes that, to be transformative, empowerment needs to be reembedded within South Africa as a multiscalar, multidimensional dialogue and, while recognising the continuation of structural constraints, positions the local as the critical scale at which to initiate broader social change.